Preferensi Masyarakat Terhadap Implikasi Konstruksi Terapung Sebagai Hunian Tangguh Banjir - Muhammad Ikhlasul Amal; Dewi Larasati (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2025)
Flooding and rising sea levels increasingly threaten residential areas in Indonesia, causing severe property damage and displacement. One potential solution is floating housing, yet its adoption remains limited due to various challenges. This study aims to assess community preferences and perceptions regarding floating housing, identifying perceived benefits and barriers to its implementation. Using a Likert-scale survey, data were collected to evaluate public opinion on safety, feasibility, and accessibility. Results indicate that communities recognize floating housing as a viable flood mitigation strategy, offering resilience and security. However, concerns about high construction costs and complex designs hinder wider acceptance. These findings highlight the need for cost-effective and simplified designs to improve feasibility. The study provides valuable insights for policymakers, architect, engineers, and urban planners in promoting sustainable flood-resilient housing.